Exploring nurse and patient perspectives on WeChat-based prenatal education in Chinese public hospitals: a qualitative inquiry - Yushi He; Guangmei Fan; Guangrui Fan; Dandan Liu (BMC Nursing)
Abstract Background With the increasing digitization of healthcare, WeChat has emerged as a popular platform for delivering prenatal education in China. While studies have shown its potential benefits, few investigations systematically explore how nurses implement WeChat-based prenatal education and how pregnant women engage with these interventions within public hospital settings. Understanding both provider and patient perspectives is critical for developing equitable, effective digital maternal care. Methods A qualitative exploratory design was employed in four public hospitals in Shanxi Province, China. Seventeen obstetric nurses and eight pregnant women participated in semi-structured interviews between March and August 2024. Data were analyzed using thematic analysis to identify commonalities and divergences between nurse-driven and patient-driven experiences. Results Nurses perceived WeChat as extending their professional reach beyond physical clinic hours and enhancing patient education, aligning with the Technology Acceptance Model constructs of perceived usefulness and ease of use. However, organizational constraints, digital training gaps, and blurred work–life boundaries posed challenges. Pregnant women similarly recognized WeChat’s convenience for quick clarifications and access to nurse-vetted information, yet wide variations in digital health literacy led to uneven engagement. Cultural factors, such as extended family involvement and preferences for in-person consultations, further influenced both nurse and patient usage patterns. Despite these challenges, participants converged on WeChat’s value as a complementary platform that could reduce clinic visits, offer immediate reassurance, and bolster continuity of care. Conclusion WeChat-based prenatal education holds significant promise for improving maternal health outcomes by facilitating frequent, real-time communication between nurses and expectant mothers. Nonetheless, the findings underscore the need for hospital-level policies, structured training programs, and culturally sensitive strategies to address privacy concerns, manage workloads, and reduce digital disparities. An integrated approach that combines nurse acceptance and patient digital literacy is essential to fully harness WeChat’s potential in public hospital contexts. Implications The study highlights practical steps for enhancing digital prenatal interventions, including standardized protocols for WeChat-based interactions, comprehensive nurse training in eHealth communication, and tailored support for pregnant women with limited digital skills. Such interventions can inform wider policymaking on telehealth and guide technology developers in creating user-friendly, secure digital platforms that optimize maternal care and reduce health inequities. Clinical trial number Not applicable.